Cell Line and DNA Biobank From Patients Affected by Genetic Diseases. (24th July 2014) - Filocamo, Mirella; Mazzotti, Raffaella; Corsolini, Fabio; Stroppiano, Marina; Stroppiana, Giorgia; Grossi, Serena; Lualdi, Susanna; Tappino, Barbara; Lanza, Federica; Galotto, Sara; Biancheri, Roberta
The Bioresource, presently storing 10, 279 biospecimens, was initially established in 1976 as a private laboratory-collection to maintain rare mutant cell lines from genetic-metabolic diseases. Shortly afterwards, however, data from the sample collection was organised in a database and the sample collection was released to the scientific community. The Biobank has received Telethon grants since 1993, as individual facility, and from 2008 as part of the Telethon Network of Genetic Biobanks (http://www.biobanknetwork.org ). In 2010, the Biobank has obtained official recognition from Regione Liguria. The Biobank has always provided essential services by establishing, analysing, maintaining, and distributing biospecimens from patients affected by rare genetic diseases. Up to now, the contribution of the Biobank to the scientific community has been expressed in acknowledgement notes in 145 scientific manuscripts.